Media Development Fraction Pop Up Book Augmented Reality Based Fraction Material To Improve Numeracy Skills - Muti'ah, Kuni; Alfi, Cindya; Fatih, Mohamad (FKIP-Universitas Riau, 2024)
Numeracy skills must be owned by students to be able to face the challenges in the 21st century. Improving numeracy skills in students can be done in learning activities at school by using learning media that are in accordance with the development of the times, one of which is by using the Fraction Pop Up Book media based on Augmented Reality . This study was conducted with the aim of determining the level of validity, feasibility and attractiveness of the Augmented Reality-based Fraction Pop-Up Book media and also to determine the increase in students' numeracy skills after learning using the developed media. This study is included in research & development (R&D) research using the Borg and Gall development model using 7 stages. This study was conducted at SDN Tlogo 02 Blitar in class 3 with a total of 33 students. This study was developed using several instruments, namely: interviews, questionnaires, tests and documentation. The results of this study show that researchers get a score of 100% from material experts, 93.75% from media experts and 87.5% from language experts. This shows that the media developed by researchers is valid media and can be used without requiring revision. The media is also a very interesting media with a percentage score of 94.61%. Students' numeracy skills also increased in the moderate category.